1986
DOI: 10.1523/jneurosci.06-12-03640.1986
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of galanin-like immunoreactivity with catecholamines, 5- hydroxytryptamine, GABA and neuropeptides in the rat CNS

Abstract: The coexistence of galanin (GAL)-like immunoreactivity (LI) with markers for catecholamines, 5-hydroxytryptamine (5-HT), GABA, or some neuropeptides was mapped in the rat CNS by using adjacent sections, as well as by elution-restaining and double-labeling immunocytochemistry. Many instances of coexistence were observed, but there were also numerous GAL-positive cell body populations displaying distributions similar to those of these markers but without apparent coexistence. In the hypothalamic arcuate nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
257
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(271 citation statements)
references
References 57 publications
12
257
0
1
Order By: Relevance
“…In this context, the neuropeptide galanin (Tatemoto et al, 1983) is of particular interest, since it coexists with NA in the locus coeruleus (LC) and with 5-HT in the dorsal raphe (DR) nucleus (Melander et al, 1986;Xu and Hökfelt, 1997;Xu et al, 1998b). Electrophysiological, behavioral, and neurochemical studies have shown that galanin exerts modulatory (mainly inhibitory) effects on both the noradrenergic and serotonergic systems (Seutin et al, 1989;Sevcik et al, 1993;Pieribone et al, 1995;Xu et al, 1998c;Razani et al, 2001;Kehr et al, 2002;see Ö gren et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the neuropeptide galanin (Tatemoto et al, 1983) is of particular interest, since it coexists with NA in the locus coeruleus (LC) and with 5-HT in the dorsal raphe (DR) nucleus (Melander et al, 1986;Xu and Hökfelt, 1997;Xu et al, 1998b). Electrophysiological, behavioral, and neurochemical studies have shown that galanin exerts modulatory (mainly inhibitory) effects on both the noradrenergic and serotonergic systems (Seutin et al, 1989;Sevcik et al, 1993;Pieribone et al, 1995;Xu et al, 1998c;Razani et al, 2001;Kehr et al, 2002;see Ö gren et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…GAL is present in the NTS where it is costored in catecholaminergic cells being coreleased with adrenaline or noradrenaline (Melander et al, 1986) and its role on central cardiovascular regulation it has been clearly established (Diaz-Cabiale et al, 2005;Harfstrand et al, 1987). In addition, it has been demonstrated that GAL act as a neurotransmitter in the NTS (Tan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2001; Xu, X.J., Hokfelt, T., et al 2000) . In the brain, galanin co-exists with other neurotransmitters like catecholamines, GABA and 5-hydroxytryptamine (Melander, T., Hokfelt, T., et al 1986), and is thought to act by modifying the release of these neurotransmitters. Three receptors for galanin have been cloned, GalR1-3 (Branchek, T., Smith, K.E., et al 1998;Branchek, T.A., Smith, K.E., et al 2000;Iismaa, T.P.…”
Section: Introductionmentioning
confidence: 99%
“…In the rat hippocampus, a common structure of seizure generation in human temporal lobe epilepsy, galanin is found mainly in noradrenergic fibers stemming from the locus coeruleus (Gabriel, S.M., Knott, P.J., et al 1995;Melander, T., Staines, W.A., et al 1986;Xu, Z.Q., Shi, T.J., et al 1998), but there is also evidence 5 for cholinergic and serotonergic inputs (Gabriel, S.M., Knott, P.J., et al 1995;Melander, T., Hokfelt, T., et al 1986;Melander, T., Staines, W.A., et al 1985).…”
Section: Introductionmentioning
confidence: 99%